Synthesis Silica Nanoparticles by Sol-Gel Method : Thermal Stability Study - Siswanto
Uniform particle size in nanoscale is very important in the field of science and technology. One of the materials that be interested to researchers today is silica nanoparticles (SNp). SNp can be applied for absorbents, catalyst support, and drug delivery purpose. However, the application is limited by the structure stability of the material. Stability of the material can be affected by heat / thermal. In this research, SNp synthesized by sol-gel method then studied the thermal stability. SNp synthesized by Tetraethyl Orthosilicate (TEOS). TEOS is hydrolyzed by NH3 catalysts in the ethanol solvent for 24 hours, then evaporated at room temperature to form a gel. Silica gel which has hardened ground up into powder. After that, Silica powder conditioned in vacuum and different temperatures (room temperature and 300 ° C) to study the thermal stability. Result of adsorption isotherm analysis showed synthesized SNp has mesopore. Analysis by Brunauer-Emmett-Teller (BET) approach showed the surface area of SNp conditioned in vacuum at room temperature and 300 °C are respectively 454 m2/g and 556 m2/g. Analysis by Density Functional Theory (DFT) approach shows the pore size is 3-6 nm and the distribution reached 0.59 cc/g/nm and 0.1 cc/g/nm. The difference of surface area and pore distribution of the SNp which conditioned in vacuum at room temperature and 300 ° C showed that the SNp structure changes. It can be concluded that the SNp is not stable in high temperature conditions.